2018
DOI: 10.7320/flmedit28.233
|View full text |Cite
|
Sign up to set email alerts
|

Solunto archaeological park in Sicily: life under mosaic tesserae

Abstract: Rotolo, V., De Caro, M. L., Giordano, A. & Palla, F.: Solunto archaeological park in Sicily: life under mosaic tesserae. -Fl. Medit. 28: 233-245. 2018. -ISSN: 1120-4052 printed, 2240-4538 online.Biodeterioration is a complex process induced by the growing and metabolic activity of a wide range of macro and microorganisms, becoming a revelling problem also for the mosaic tesserae of "Casa di Leda" in the Greco -Roman site of Solunto in Sicily. In this case-study, a thick biofilm inducing a deep alteration of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Previous studies have evaluated the antimicrobial activity of essential oils or their compounds against microorganisms on over-ground cultural heritage objects [39,40], mural paintings [41][42][43] or mosaic tesserae [44]. In detail, Stupar et al [39], in a similar approach with the current study, applied the microdilution method to define the MIC of O. vulgare, Rosmarinus officinalis and Lavantula angustifolia EOs in comparison with the conventional BAC on five fungal strains isolated from cultural heritage objects [39].…”
Section: Mic and Nic Of The Most Effective Eosmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have evaluated the antimicrobial activity of essential oils or their compounds against microorganisms on over-ground cultural heritage objects [39,40], mural paintings [41][42][43] or mosaic tesserae [44]. In detail, Stupar et al [39], in a similar approach with the current study, applied the microdilution method to define the MIC of O. vulgare, Rosmarinus officinalis and Lavantula angustifolia EOs in comparison with the conventional BAC on five fungal strains isolated from cultural heritage objects [39].…”
Section: Mic and Nic Of The Most Effective Eosmentioning
confidence: 96%
“…They have demonstrated that basil EO was the most effective against all the tested strains, able to inhibit their growth at 1.25 µL/mL (i.e., 0.125% v/v). Finally, Rotolo et al [44] have evaluated two EOs (Thymus vulgaris and O. vulgare preliminarily in vitro (agar disc diffusion method) and after ex situ and in situ to control the biofilm (bacteria, fungi, cyanobacteria and green algae) colonization on the mosaic tesserae in the Greco-Roman archeological site of Solunto, Sicily (Italy). T. vulgaris solution was proven to be the best diffused, strongly influencing the biofilm liveliness, however the tested concentration was high (15% EO).…”
Section: Mic and Nic Of The Most Effective Eosmentioning
confidence: 99%
See 1 more Smart Citation
“…Three in vitro methods, Agar disc diffusion, Well-plates diffusion, and Microdilution in micro-titer plates [38,43,44] were performed:…”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%
“…Gas chromatographic analysis reveal several bioactive molecules such as carvacrol and thymol, beside cineol and thymol methilester, p-cymene and terpinol, borneol, geraniol, linalool alcohols, acetate and linalyl esters. Particularly, essential oils of O. vulgare and T. vulgaris were successful applied to counteract fungal colonization (Aspergillus flavus, Aspergillus niger, Penicillium chrysogenum) or insect infestation (Anobium punctatum) on wooden artworks [12][13][14], as well as to affect the development and vitality of a complex biofilm revealed under the tiles of the mosaic floor in the Solunto Archaeological Park, Sicily [15]. Furthermore, I. crithmoides EO shows antibacterial activity vs Georgenia sp., Ornthinibacillus sp.…”
Section: Introductionmentioning
confidence: 99%